Phytochemical study of the Genus Salpichroa (Solanaceae), chemotaxonomic considerations, and biological evaluation in prostate and breast cancer cells - Basso, Ana Valentina (2017)
Twelve Salpichroa taxa have been phytochemically analyzed. From the aerial parts of S. scandens, four known salpichrolides A, C, I, S, and an unreported withanolide named salpichrolide V (1), were isolated. In S. dependens, S. gayi, S. glandulosa subsp. glandulosa, S. glandulosa subps. weddellii, S. leucantha, S. micrantha, S. microloba, S. proboscidea, S. ramosissima, S. tristis var. tristis, and S. weberbauerii, no withanolides were found. The chemical content of ca. 85% of the Salpichroa taxa is in agreement with molecular studies, which suggest that Salpichroa and Jaborosa, a genus considered morphologically close to Salpichroa, are distant in the systematic of the Solanoideae subfamily. Moreover, the in vitro cytotoxic activity of a set of natural salpichrolides and derivatives was examined against two prostate carcinoma cell lines (PC3 and LNCaP) and two human breast cancer cell lines (MCF-7 and T47D). Several compounds showed moderate activity (IC50 = 64.91 – 29.97 μm).